Social capital and access to (natural) resources and markets along the Brazil nut (Bertholletia excelsa) value chain in the Lower Amazon basin, Pará - Cunha, Marcelo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The aim of this study is to understand the relationships between social capital and access to (natural) resources and markets in the case of Brazil nut value chain actors in the meso-region of the Lower Amazon, with a focus on quilombola communities from Oriximiná and the environs of the market in Óbidos, Pará. The analytical framework combines conceptual analysis with empirical observations to improve understanding of the relationships among the variables in question and provides scientific input for co-development of the value chain. Socioeconomic and environmental data were collected through interviews with agroextrativistas and group interviews at community level. Results highlight the existence of ‘bonding social capital’ which unites individuals from the same community and ‘linking’ and ‘bridging social capital’ that connect them to downstream chain actors, potentially facilitating access to (natural) resources and markets. Mainly due to trust, trade relationships along the Brazil nut value chain generate significant mutual benefits among the Associação dos Moradores da Comunidade Remanescente de Quilombo de Cachoeira Porteira (AMOCREQ) from the quilombola community Cachoeira Porteira in Oriximiná and the firm Mundial Exportadora in Óbidos, despite the shorter distances to the Oriximiná market.
Keywords: Access to resources; Social capital; Brazil nut value chain; Non-timber forest product